Optimizing machine-learning-based NILM: A comparative analysis of wavelet feature extraction for high-accuracy appliance classification - Nathan Morris; James Gopsill; Maria Valero; Sam Williamson; Ben Hicks (Energy and Buildings, 2026)

Human health risk of particle exposure in outdoor environments in southwestern Pennsylvania - Abdulrahman N. Alobireed; Samantha C. Totoni; Linda M. Wigington; James P. Fabisiak; Nesta Bortey-Sam (Environmental Science and Pollution Research, 2026)

Bone Marrow Mesenchymal Stem Cell Extracellular Vesicle Treatment of Respiratory Failure from COVID-19: Endpoint Analysis of Expanded Access Safety Trial - Vikram Sengupta; Sascha Qian; John T. Ransom; Sam Suzuki; David J. Park; Timothy I. Melson; Brian P. Williams; James J. Walsh; Mustafa Awili; Jack M. Mann; Timothy A. Moseley (Stem Cell Reviews and Reports, 2026)

The roles of actors in nature-positive transformations - Jennifer Yarnold; Josie Carwardine; Sandra Oliver; Yuwan Malakar; James D. Langston; Ilisapeci Lyons; Anthony O’Grady; Michael Dunlop; Piers Dunstan; Sam Nicol (Ambio, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The GPR139 agonist TAK-041 produces time-dependent alterations to cerebral blood flow and reward system function in patients with schizophrenia: a randomised placebo-controlled trial - Peter C. T. Hawkins; Adam J. Schwarz; James M. Stone; Fiona Pepper; James Gilleen; Sam Gijsen; Ndabezinhle Mazibuko; Dimitrios Arkilo; Wei Yin; Jingtao Wu; Polyna Khudyakov; Rhett Behrje; et al. (Psychopharmacology, 2026)
The negative and cognitive symptoms of schizophrenia are predictive of quality of life and functional recovery, but there are no approved drug options that target these symptoms directly. TAK-041 (also known as NBI-1065846) is a selective and potent small-molecule agonist of GPR139, an orphan G-protein-coupled receptor, which has been shown to reverse deficits related to negative and cognitive symptoms in animal models. In this proof-of-activity study to evaluate the effects of TAK-041 on motivational anhedonia, 23 adults with schizophrenia experiencing moderate to severe negative symptoms were administered a single 40 mg or 160 mg dose of TAK-041 in a randomised, double-blind, placebo-controlled, two-period crossover design. Functional magnetic resonance imaging (fMRI) assessment of reward function (monetary incentive delay [MID] task) and cerebral blood flow (CBF), as well as cognitive assessment with the Brief Assessment of Cognition in Schizophrenia (BACS) tool, were performed 3 h post dose and after 14 days. There was no significant effect of TAK-041 compared with placebo on BACS score at either timepoint. There was also no significant effect of TAK-041 on MID fMRI at day 1; however, at day 14, TAK-041 produced an increase in reward anticipatory activity in the ventral striatum compared with placebo. There was a significant decrease in CBF throughout the brain at day 1 that then reversed, resulting in a relative increase at day 14, compared with placebo. At day 14 there was a significant interaction between drug and CBF on reward anticipatory BOLD, indicating that drug-related changes to CBF may partially contribute to the observed BOLD effects (although the main effect of drug on the BOLD signal remained significant after including CBF as a covariate in the model). These data indicate that TAK-041 produces detectable changes in both CBF and reward task related fMRI signal in brain regions linked with symptoms and treatment response in schizophrenia. IND Number: 130074| EudraCT Number: 2017-001084-20| Clincaltrails.gov registry: NCT03319953.

Spaced out: An economic framework to explore the impacts of PV panel spacing on large-scale farming in Colorado - Brian Mirletz; James McCall; Samantha Bryan; Dala Al Mukhaini; Claire Nguyen; Sam Anderson; Stephan Weiler; Jordan Macknick (Agricultural Systems, 2026)

A framework for assessing global health impacts of polar change: An urgent call for interdisciplinary research - Netra Naik; Karol Bot; Gail Whiteman; Lora E. Fleming; Karyn Morrissey; Richard Garth James Bellerby; Sam Dupont; Dmitry Yumashev; Susana Hancock; Brendan M. Rogers; Kristie L. Ebi; Joacim Rocklöv (Ambio, 2026)
Research on the human health risks of climate change is expanding, yet the influence of polar region shifts on these risks remains underexplored. This paper presents a framework to assess global and regional health risks stemming from polar physical changes. The polar regions are experiencing rapid environmental transformations, including melting ice, ocean warming, ocean acidification, permafrost thaw, intensifying wildfires, and alterations to jet streams, ocean currents. These changes can amplify global risks, affecting human health even in distant regions. The paper identifies potential cascading impacts on health and well-being via drivers such as extreme weather, heat stress, air, water quality, food supply, safety, vector ecology, and sea-level rise. A scoping review was conducted by an international team of public health and polar experts to support thematic categorization of regional and global health risks. The paper advocates integrating these amplified risks into health impact assessments through interdisciplinary, international collaboration to inform future policy responses.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Evaluating projections of the costs of pesticide regulation: Evidence from California's chlorpyrifos withdrawal - Benjamin W Lee; Kevi Mace; James Keeler; Sam Raburn; Daniel Schuurman; Yanan Zheng; Rachael Goodhue (Agricultural Systems, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Utilising on-farm risk assessment data for the management of Johne’s disease in dairy cattle in Northern Ireland - Emma Nicole Taylor-Holt; Sam Strain; Nicholas Mark Taylor; Sitira Williams; Nicholas Wheelhouse; James Hanks; Peter Guy Orpin; David C. Rose; Abel Bulamu Ekiri (Preventive Veterinary Medicine, 2025)

The influence of artificial reef structural complexity on fish assemblage composition - Brooke T. Marshall; Sam R. Russell; James H. Florisson; Benjamin J. Saunders; Stephen J. Newman; Euan S. Harvey (Marine Environmental Research, 2025)

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Exploring policy coherence for land use transformations: The case of Scotland - Hebe Nicholson; Kirsty Blackstock; Jean Boucher; James Glendinning; Alexa Green; Alba Juarez-Bourke; Stan Martinat; Graciela Martínez Sánchez; Keith Matthews; Ian Merrell; Sam Poskitt; Steven Thomson (Journal of Environmental Management, 2025)

Coral colony abundances and sizes as indicators of reef health in subtropical Hong Kong waters - Hai Xin Loke; Yip Hung Yeung; Sam King Fung Yiu; James Y. Xie; Jian-Wen Qiu (Marine Pollution Bulletin, 2024)

Health impact of policies to reduce agriculture-related air pollutants in the UK: The relative contribution of change in PM2.5 exposure and diets to morbidity and mortality - Silvia Pastorino; Ai Milojevic; Rosemary Green; Rachel Beck; Edward Carnell; Patricia Eustachio Colombo; Tom Misselbrook; Mark Miller; Stefan Reis; Sam Tomlinson; Massimo Vieno; James Milner (Environmental Research, 2024)

The accuracy of Eclipse AXB and AAA dose algorithms with dental amalgam - Sam Potter; Carine Maxwell; James Rijken (Physical and Engineering Sciences in Medicine, 2024)

Immune gene regulation is associated with age and environmental adversity in a nonhuman primate - Marina M. Watowich; Christina E. Costa; Kenneth L. Chiou; Elisabeth A. Goldman; Rachel M. Petersen; Sam Patterson; Melween I. Martínez; Kirstin N. Sterner; Julie E. Horvath; Michael J. Montague; Michael L. Platt; Lauren J. N. Brent; et al. (Molecular Ecology, 2024)
Phenotypic aging is ubiquitous across mammalian species, suggesting shared underlying mechanisms of aging. Aging is linked to molecular changes to DNA methylation and gene expression, and environmental factors, such as severe external challenges or adversities, can moderate these age‐related changes. Yet, it remains unclear whether environmental adversities affect gene regulation via the same molecular pathways as chronological, or ‘primary’, aging. Investigating molecular aging in naturalistic animal populations can fill this gap by providing insight into shared molecular mechanisms of aging and the effects of a greater diversity of environmental adversities – particularly those that can be challenging to study in humans or laboratory organisms. Here, we characterised molecular aging – specifically, CpG methylation – in a sample of free‐ranging rhesus macaques living off the coast of Puerto Rico ( n samples = 571, n individuals = 499), which endured a major hurricane during our study. Age was associated with methylation at 78,661 sites (31% of all sites tested). Age‐associated hypermethylation occurred more frequently in areas of active gene regulation, while hypomethylation was enriched in regions that show less activity in immune cells, suggesting these regions may become de‐repressed in older individuals. Age‐associated hypomethylation also co‐occurred with increased chromatin accessibility while hypermethylation showed the opposite trend, hinting at a coordinated, multi‐level loss of epigenetic stability during aging. We detected 32,048 CpG sites significantly associated with exposure to a hurricane, and these sites overlapped age‐associated sites, most strongly in regulatory regions and most weakly in quiescent regions. Together, our results suggest that environmental adversity may contribute to aging‐related molecular phenotypes in regions of active gene transcription, but that primary aging has specific signatures in non‐regulatory regions.

Reduction of large vessel traffic improves water quality and alters fish habitat-use throughout a large river - Michael J. Spear; Brandon S. Harris; Taylor A. Bookout; Brian S. Ickes; Kathi Jo Jankowski; Levi E. Solomon; Kristopher A. Maxson; Andrya L. Whitten Harris; Andrew T. Mathis; Sam J. Schaick; Jesse A. Williams; Jason A. DeBoer; et al. (Science of The Total Environment, 2024)

Challenges for the management of Johne’s disease in the UK: Expectation management, space, ‘free riding’, and vet-farmer communication - Rosie Morrison; James Hanks; Peter Guy Orpin; Sam Strain; Emma Nicole Taylor; David Christian Rose (Preventive Veterinary Medicine, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The impact of uninterrupted sitting on central and peripheral cardiovascular function in pre-menopausal and post-menopausal women - Arsalan Moinuddin; Keeron Stone; Louise Turner; Craig Paterson; Nicky Hall; Anne Daykin; Sam Lucas; James Faulkner; Simon Fryer (European Journal of Applied Physiology, 2024)

Temperate coastal fish shows resilience to extreme low pH in early larval stages - Carla Edworthy; Nicola C. James; Warren M. Potts; Murray I. Duncan; Sam Dupont (Journal of Experimental Marine Biology and Ecology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Application of Advanced Modeling Approaches Supporting Generic Product Development Under GDUFA for Fiscal Year 2023 - Eleftheria Tsakalozou; Yuqing Gong; Andrew Babiskin; Meng Hu; Youssef Mousa; Ross Walenga; Fang Wu; Miyoung Yoon; Sam G. Raney; James E. Polli; Anna Schwendeman; Vishalakshi Krishnan; et al. (The AAPS Journal, 2024)

Social incentives as nudges for agricultural knowledge diffusion and willingness to pay for certified seeds: Experimental evidence from Uganda - Julius Okello; Kelvin Mashisia Shikuku; Carl Johan Lagerkvist; Jens Rommel; Wellington Jogo; Sylvester Ojwang; Sam Namanda; James Elungat (Food Policy, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Combined effect of salinity and hypoxia on digestive enzymes and intestinal microbiota in the oyster Crassostrea hongkongensis - Zhe Xie; Yuting Li; Kai Xiong; Zhihan Tu; Khor Waiho; Chuangye Yang; Yuewen Deng; Saishuai Li; James K.H. Fang; Menghong Hu; Sam Dupont; Youji Wang (Environmental Pollution, 2023)

Correction: Seasonal Differences in the Encounter Rate of the Fat-Tailed Dwarf Lemur (Cheirogaleus medius) in the Transitional Forests of Northwest Madagascar: Implications for Reliable Population Density Assessment - Daniel Hending; Heriniaina Randrianarison; Niaina Nirina Mahefa Andriamavosoloarisoa; Christina Ranohatra-Hending; James Sedera Solofondranohatra; Haja Roger Tongasoa; Herinirina Tahina Ranarison; Victoria Gehrke; Natacha Andrianirina; Marc Holderied; Grainne McCabe; Sam Cotton (International Journal of Primatology, 2023)

Seasonal Differences in the Encounter Rate of the Fat-Tailed Dwarf Lemur (Cheirogaleus medius) in the Transitional Forests of Northwest Madagascar: Implications for Reliable Population Density Assessment - Daniel Hending; Heriniaina Randrianarison; Niaina Nirina Mahefa Andriamavosoloarisoa; Christina Ranohatra-Hending; James Sedera Solofondranohatra; Haja Roger Tongasoa; Herinirina Tahina Ranarison; Victoria Gehrke; Natacha Andrianirina; Marc Holderied; Grainne McCabe; Sam Cotton (International Journal of Primatology, 2023)
Primate encounter rates often vary throughout the year due to seasonal differences in activity, ecology, and behaviour. One notably extreme behaviour is continuous hibernation. Although a rare adaptation in primates, the dwarf lemurs of Madagascar (genus Cheirogaleus ) enter obligate hibernation each year during the dry season, after spending the wet season consuming high-energy foods. Whilst seasonal changes in activity in some Cheirogaleus populations are well-known, many species remain little-studied, and there is no specific information on their encounter rates, nor when they enter and emerge from hibernation. This uncertainty critically affects reliable calculation of population density estimates for these highly threatened lemurs. In this study, we assessed how encounter rates of the fat-tailed dwarf lemur ( C. medius ) vary seasonally in the transitional forests of the Sahamalaza-Iles Radama National Park, northwest Madagascar, during a 4-year period. We established a system of line transects ( N = 60) throughout our study area, on which we conducted distance sampling of C. medius . We then used our distance sampling data to calculate encounter rate and population density data. We found encounter rates of C. medius to be significantly higher during the wet season compared with the dry season. Furthermore, encounter rates of C. medius were particularly low from May–August. These results provide some evidence to suggest the time period that C. medius hibernate in Sahamalaza-Iles Radama National Park. These findings underpin the importance of careful study design when surveying threatened species with seasonal differences in activity, such as those that hibernate. This study also demonstrates the importance of species-specific behavioural data for accurate population density assessment, which is required to inform conservation action.

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

Ambient temperature and air pollution associations with suicide and homicide mortality in California: A statewide case-crossover study - Md Mostafijur Rahman; Melissa Lorenzo; George Ban-Weiss; Zainab Hasan; Mehjar Azzouz; Sandrah P. Eckel; David V. Conti; Fred Lurmann; Hannah Schlaerth; Jill Johnston; Joseph Ko; Lawrence Palinkas; et al. (Science of The Total Environment, 2023)

Exploring the risks and benefits of flexibility in biodiversity offset location in a case study of migratory shorebirds - Nicole Shumway; Megan I. Saunders; Sam Nicol; Richard A. Fuller; Noam Ben‐Moshe; Takuya Iwamura; Sun W. Kim; Nicholas J. Murray; James E. M. Watson; Martine Maron (Conservation Biology, 2023)
Biodiversity offsets aim to counterbalance the residual impacts of development on species and ecosystems. Guidance documents explicitly recommend that biodiversity offset actions be located close to the location of impact because of higher potential for similar ecological conditions, but allowing greater spatial flexibility has been proposed. We examined the circumstances under which offsets distant from the impact location could be more likely to achieve no net loss or provide better ecological outcomes than offsets close to the impact area. We applied a graphical model for migratory shorebirds in the East Asian–Australasian Flyway as a case study to explore the problems that arise when incorporating spatial flexibility into offset planning. Spatially flexible offsets may alleviate impacts more effectively than local offsets; however, the risks involved can be substantial. For our case study, there were inadequate data to make robust conclusions about the effectiveness and equivalence of distant habitat‐based offsets for migratory shorebirds. Decisions around offset placement should be driven by the potential to achieve equivalent ecological outcomes; however, when considering more distant offsets, there is a need to evaluate the likely increased risks alongside the potential benefits. Although spatially flexible offsets have the potential to provide more cost‐effective biodiversity outcomes and more cobenefits, our case study showed the difficulty of demonstrating these benefits in practice and the potential risks that need to be considered to ensure effective offset placement.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A Survey of the Metabolic Landscape of the Developing Cerebellum at Single-Cell Resolution - James R. Krycer; Sam P. Nayler (The Cerebellum, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Editorial: Working Towards a Blue Future: Promoting Sustainability, Environmental Protection and Marine Management: Examples from the UK Government Blue Belt Programme and Current International Initiatives - Paul Whomersley; James Bell; Elizabeth Clingham; Martin A. Collins; David A. Feary; Joanna Stockill; Sam Weber; Oliver Yates; Kylie Bamford (Frontiers in Marine Science, 2022)

An Assessment of Economic Viability of the Ascension Island Tuna Longline Fishery Management: Implications for Marine Protected Area Planning and Future Fisheries Management - Angela Muench; Elena Mengo; Sam Weber; Diane Baum; Andrew James Richardson; Hannah Thomas; Paul Whomersley (Frontiers in Marine Science, 2022)
The designation of large scale marine protected areas (MPAs) has increased in recent years to address global issues such as biodiversity loss and the conservation of vulnerable marine habitats. While designing a large scale MPAs in the Exclusive Economic Zone (EEZ) of Ascension Island, the monitoring and enforcement costs were estimated for the two options under consideration: partial closure or full closure of the EEZ for the international commercial fleet. It was found that number of licenses to be sold to the international fleet to allow them access to the EEZ of Ascension Island would need to be increased to fund the monitoring and enforcement cost in case of a partial closure of the EEZ of Ascension Island. In this study, the future economic viability of the licensed big eye tuna fishery was addressed. The study explored economic drivers thought to be linked to license sales. It was shown that cost of licenses had not caused the observed decline in license sales but a shift in consumer demand toward lighter tuna species resulted in a decrease in Japanese imports for bigeye tuna ( Thunnus obesus ). This change in demand led to global changes in fishing effort and a drop in demand for licenses to fish within the Ascension Island EEZ. This study provided a valuable insight into the economic viability of the bigeye tuna fishery within the Ascension Island EEZ which informed the subsequent decision to close the bigeye tuna fishery as part of the designation of an Ascension Island highly protected large-scale MPA.

Clear consensus among international public for government action at COP26: patriotic and public health frames produce marginal gains in support - Tessa Buchanan; James Ackland; Sam Lloyd; Sander van der Linden; Lee de-Wit (Climatic Change, 2022)

Research and Education Needs for Complex Generics - Sydney Stern; Jill Coghlan; Vishalakshi Krishnan; Sam G. Raney; Andrew Babiskin; Wenlei Jiang; Robert Lionberger; Xiaoming Xu; Anna Schwendeman; James E. Polli (Pharmaceutical Research, 2021)
Complex generics are generic versions of drug products that generally have complex active ingredients, complex formulations, complex routes of delivery, complex dosage forms, are complex drug-device combination products, or have other characteristics that can make it complex to demonstrate bioequivalence or to develop as generics. These complex products (i.e. complex generics) are an important element of the United States (U.S.) Food and Drug Administration’s (FDA’s) Generic Drug User Fee Amendments (GDUFA) II Commitment Letter. The Center for Research on Complex Generics (CRCG) was formed by a grant from the FDA to address challenges associated with the development of complex generics. To understand these challenges, the CRCG conducted a “Survey of Scientific Challenges in the Development of Complex Generics”. The three main areas of questioning were directed toward which (types of) complex products, which methods of analysis to support a demonstration of bioequivalence, and which educational topics the CRCG should prioritize. The survey was open to the public on a website maintained by the CRCG. Regarding complex products, the top three selections were complex injectables, formulations, and nanomaterials; drug-device combination products; and inhalation and nasal products. Regarding methods of analysis, the top three selections were locally-acting physiologically-based pharmacokinetic modeling; oral absorption models and bioequivalence; and data analytics and machine learning. Regarding educational topics, the top three selections were complex injectables, formulations, and nanomaterials; drug-device combination products; and data analytics, including quantitative methods and modeling & simulation. These survey results will help prioritize the CRCG’s initial research and educational initiatives.

Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - S. James Reynolds; Colin P. Wearn; B. John Hughes; Roger C. Dickey; Lucy J. H. Garrett; Sean Walls; Fay T. Hughes; Nicola Weber; Sam B. Weber; Eliza H. K. Leat; Kenickie Andrews; Jaime A. Ramos; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns ( Onychoprion fuscatus ) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.

Local administration of submicron particle paclitaxel to solid carcinomas induces direct cytotoxicity and immune-mediated tumoricidal effects without local or systemic toxicity: preclinical and clinical studies - Shelagh Verco; Holly Maulhardt; Michael Baltezor; Emily Williams; Marc Iacobucci; Alison Wendt; James Verco; Alyson Marin; Sam Campbell; Paul Dorman; Gere diZerega (Drug Delivery and Translational Research, 2021)
This report describes local administration of submicron particle paclitaxel (SPP) (NanoPac®: ~ 800-nm-sized particles with high relative surface area with each particle containing ~ 2 billion molecules of paclitaxel) in preclinical models and clinical trials evaluating treatment of carcinomas. Paclitaxel is active in the treatment of epithelial solid tumors including ovarian, peritoneal, pancreatic, breast, esophageal, prostate, and non-small cell lung cancer. SPP has been delivered directly to solid tumors, where the particles are retained and continuously release the drug, exposing primary tumors to high, therapeutic levels of paclitaxel for several weeks. As a result, tumor cell death shifts from primarily apoptosis to both apoptosis and necroptosis. Direct local tumoricidal effects of paclitaxel, as well as stimulation of innate and adaptive immune responses, contribute to antineoplastic effects. Local administration of SPP may facilitate tumor response to systemically administered chemotherapy, targeted therapy, or immunotherapy without contributing to systemic toxicity. Results of preclinical and clinical investigations described here suggest that local administration of SPP achieves clinical benefit with negligible toxicity and may complement standard treatments for metastatic disease. Graphical abstract

Large potential for crop production adaptation depends on available future varieties - Florian Zabel; Christoph Müller; Joshua Elliott; Sara Minoli; Jonas Jägermeyr; Julia M. Schneider; James A. Franke; Elisabeth Moyer; Marie Dury; Louis Francois; Christian Folberth; Wenfeng Liu; et al. (Global Change Biology, 2021)
Climate change affects global agricultural production and threatens food security. Faster phenological development of crops due to climate warming is one of the main drivers for potential future yield reductions. To counter the effect of faster maturity, adapted varieties would require more heat units to regain the previous growing period length. In this study, we investigate the effects of variety adaptation on global caloric production under four different future climate change scenarios for maize, rice, soybean, and wheat. Thereby, we empirically identify areas that could require new varieties and areas where variety adaptation could be achieved by shifting existing varieties into new regions. The study uses an ensemble of seven global gridded crop models and five CMIP6 climate models. We found that 39% (SSP5‐8.5) of global cropland could require new crop varieties to avoid yield loss from climate change by the end of the century. At low levels of warming (SSP1‐2.6), 85% of currently cultivated land can draw from existing varieties to shift within an agro‐ecological zone for adaptation. The assumptions on available varieties for adaptation have major impacts on the effectiveness of variety adaptation, which could more than half in SSP5‐8.5. The results highlight that region‐specific breeding efforts are required to allow for a successful adaptation to climate change.

Personal Care and Cosmetic Products as a Potential Source of Environmental Contamination by Microplastics in a Densely Populated Asian City - Saidu M. Bashir; Sam Kimiko; Chu-Wa Mak; James Kar-Hei Fang; David Gonçalves (Frontiers in Marine Science, 2021)
The prevalence of microplastics in the environment has become a major global conservation issue. One primary source of environmental microplastics is personal care and cosmetic products (PCCPs) containing microbeads. The market availability of PCCPs containing microbeads and the level of contamination of coastal sediments by microplastics was studied in one of the most densely populated cities in the world, Macao in China. We found that PCCPs containing microbeads are still widely available for sale in the region, with over 70% of surveyed PCCPs containing at least one type of microbeads as an ingredient, with polyethylene (PE) being the most common one. In an estimate, the use of PCCPs in the territory may release over 37 billion microbeads per year into the environment via wastewater treatment plants. The density of microplastics in coastal sediments varied between 259 and 1,743 items/L of sediment, amongst the highest reported in the world. The fraction of < 1 mm was the most abundant, representing an average of 98.6% of the total, and correlated positively with the abundance of larger sized fragments. The results show that although environmental pollution with microplastics released from PCCPs usage is significant, other sources, namely fragmentation of larger plastic debris, likely contribute more to the issue. The study highlights the magnitude of the problem at a local level and suggests possible mitigating strategies.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Retraction Note to: Prolonged food restriction decreases body condition and reduces repeatability in personality traits in web-building spiders - James L. L. Lichtenstein; Nicholas DiRienzo; Karen Knutson; Candice Kuo; Katherine C. Zhao; Hayley A. Brittingham; Sara E. Geary; Sam Ministero; Henry K. Rice; Zachary David; Inon Scharf; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2021)

Challenges in coupling atmospheric electricity with biological systems - Ellard R. Hunting; James Matthews; Pablo Fernández de Arróyabe Hernáez; Sam J. England; Konstantinos Kourtidis; Kuang Koh; Keri Nicoll; R. Giles Harrison; Konstantine Manser; Colin Price; Snezana Dragovic; Michal Cifra; et al. (International Journal of Biometeorology, 2021)
The atmosphere is host to a complex electric environment, ranging from a global electric circuit generating fluctuating atmospheric electric fields to local lightning strikes and ions. While research on interactions of organisms with their electrical environment is deeply rooted in the aquatic environment, it has hitherto been confined to interactions with local electrical phenomena and organismal perception of electric fields. However, there is emerging evidence of coupling between large- and small-scale atmospheric electrical phenomena and various biological processes in terrestrial environments that even appear to be tied to continental waters. Here, we synthesize our current understanding of this connectivity, discussing how atmospheric electricity can affect various levels of biological organization across multiple ecosystems. We identify opportunities for research, highlighting its complexity and interdisciplinary nature and draw attention to both conceptual and technical challenges lying ahead of our future understanding of the relationship between atmospheric electricity and the organization and functioning of biological systems.

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Characterization of genetically complex Collaborative Cross mouse strains that model divergent locomotor activating and reinforcing properties of cocaine - Sarah A. Schoenrock; Padam Kumar; Alexander Gómez-A; Price E. Dickson; Sam-Moon Kim; Lauren Bailey; Sofia Neira; Kyle D. Riker; Joseph Farrington; Christiann H. Gaines; Saad Khan; Troy D. Wilcox; et al. (Psychopharmacology, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Advancing Observation of Ocean Biogeochemistry, Biology, and Ecosystems With Cost-Effective in situ Sensing Technologies - Zhaohui Aleck Wang; Hassan Moustahfid; Amy V. Mueller; Anna P. M. Michel; Matthew Mowlem; Brian T. Glazer; T. Aran Mooney; William Michaels; Jonathan S. McQuillan; Julie C. Robidart; James Churchill; Marc Sourisseau; et al. (Frontiers in Marine Science, 2019)

Non-Destructive Reflectance Mapping of Collagen Fiber Alignment in Heart Valve Leaflets - Will Goth; Sam Potter; Alicia C. B. Allen; Janet Zoldan; Michael S. Sacks; James W. Tunnell (Annals of Biomedical Engineering, 2019)

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic? - S. James Reynolds; B. John Hughes; Colin P. Wearn; Roger C. Dickey; Judith Brown; Nicola L. Weber; Sam B. Weber; Vitor H. Paiva; Jaime A. Ramos (Global Change Biology, 2019)
In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns ( Onychoprion fuscatus ) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift occurred during the second half of the twentieth century coinciding with an apparent population collapse of approximately 84%. After correcting for the “Suess Effect,” δ 13 C in feathers declined by ~1.5‰ and δ 15 N by ~2‰ between the 1890s and the present day, indicating that birds changed their diets markedly over the period of population decline. Isotopic niches were equally wide before and after the population collapse but isotopic mixing models suggest that birds have grown ever more reliant on nutrient‐poor squid and invertebrates as teleost fish have declined in availability. Given that sooty terns rely heavily on associations with sub‐surface predators such as tuna to catch fish prey, the rapid expansion of industrialized fisheries for these species over the same period seems a plausible mechanism. Our results suggest that changes to marine ecosystems over the past 60 years have had a dramatic impact on the ecology of the most abundant seabird of tropical oceans, and highlight the potentially pervasive consequences of large predatory fish depletion on marine ecosystem function.

From ecologically equivalent individuals to contrasting colonies: quantifying isotopic niche and individual foraging specialization in an endangered oceanic seabird - Anne E. Wiley; Sam Rossman; Peggy H. Ostrom; Christine A. M. France; Jay Penniman; Cathleen Bailey; Fern Duvall; Elise F. Zipkin; Helen F. James (Marine Biology, 2019)

Trophic declines and decadal-scale foraging segregation in three pelagic seabirds - Kaycee E. Morra; Yoshito Chikaraishi; Hasand Gandhi; Helen F. James; Sam Rossman; Anne E. Wiley; Andre F. Raine; Jessie Beck; Peggy H. Ostrom (Oecologia, 2019)

Non-auditory, electrophysiological potentials preceding dolphin biosonar click production - James J. Finneran; Jason Mulsow; Ryan Jones; Dorian S. Houser; Alyssa W. Accomando; Sam H. Ridgway (Journal of Comparative Physiology A, 2018)

Integrating count and detection–nondetection data to model population dynamics - Elise F. Zipkin; Sam Rossman; Charles B. Yackulic; J. David Wiens; James T. Thorson; Raymond J. Davis; Evan H. Campbell Grant (Ecology, 2017)
There is increasing need for methods that integrate multiple data types into a single analytical framework as the spatial and temporal scale of ecological research expands. Current work on this topic primarily focuses on combining capture–recapture data from marked individuals with other data types into integrated population models. Yet, studies of species distributions and trends often rely on data from unmarked individuals across broad scales where local abundance and environmental variables may vary. We present a modeling framework for integrating detection–nondetection and count data into a single analysis to estimate population dynamics, abundance, and individual detection probabilities during sampling. Our dynamic population model assumes that site‐specific abundance can change over time according to survival of individuals and gains through reproduction and immigration. The observation process for each data type is modeled by assuming that every individual present at a site has an equal probability of being detected during sampling processes. We examine our modeling approach through a series of simulations illustrating the relative value of count vs. detection–nondetection data under a variety of parameter values and survey configurations. We also provide an empirical example of the model by combining long‐term detection–nondetection data (1995–2014) with newly collected count data (2015–2016) from a growing population of Barred Owl ( Strix varia ) in the Pacific Northwest to examine the factors influencing population abundance over time. Our model provides a foundation for incorporating unmarked data within a single framework, even in cases where sampling processes yield different detection probabilities. This approach will be useful for survey design and to researchers interested in incorporating historical or citizen science data into analyses focused on understanding how demographic rates drive population abundance.

Assessing disparities in colorectal cancer mortality by socioeconomic status using new tools: health disparities calculator and socioeconomic quintiles - Nancy Breen; Denise Riedel Lewis; James Todd Gibson; Mandi Yu; Sam Harper (Cancer Causes & Control, 2017)

RETRACTED ARTICLE: Prolonged food restriction decreases body condition and reduces repeatability in personality traits in web-building spiders - James L. L. Lichtenstein; Nicholas DiRienzo; Karen Knutson; Candice Kuo; Katherine C. Zhao; Hayley A. Brittingham; Sara E. Geary; Sam Ministero; Henry K. Rice; Zachary David; Inon Scharf; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2016)

Down‐regulation of tissue N:P ratios in terrestrial plants by elevated CO 2 - Qi Deng; Dafeng Hui; Yiqi Luo; James Elser; Ying-Ping Wang; Irakli Loladze; Quanfa Zhang; Sam Dennis (Ecology, 2015)
Increasing atmospheric CO 2 concentrations generally alter element stoichiometry in plants. However, a comprehensive evaluation of the elevated CO 2 impact on plant nitrogen : phosphorus (N:P) ratios and the underlying mechanism has not been conducted. We synthesized the results from 112 previously published studies using meta‐analysis to evaluate the effects of elevated CO 2 on the N:P ratio of terrestrial plants and to explore the underlying mechanism based on plant growth and soil P dynamics. Our results show that terrestrial plants grown under elevated CO 2 had lower N:P ratios in both above‐ and belowground biomass across different ecosystem types. The response ratio for plant N:P was negatively correlated with the response ratio for plant growth in croplands and grasslands, and showed a stronger relationship for P than for N. In addition, the CO 2 ‐induced down‐regulation of plant N:P was accompanied by 19.3% and 4.2% increases in soil phosphatase activity and labile P, respectively, and a 10.1% decrease in total soil P. Our results show that down‐regulation of plant N:P under elevated CO 2 corresponds with accelerated soil P cycling. These findings should be useful for better understanding of terrestrial plant stoichiometry in response to elevated CO 2 and of the underlying mechanisms affecting nutrient dynamics under climate change.

Genetic basis of age-dependent synaptic abnormalities in the retina - Hitoshi Higuchi; Erica L. Macke; Wei-Hua Lee; Sam A. Miller; James C. Xu; Sakae Ikeda; Akihiro Ikeda (Mammalian Genome, 2015)

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Unexpected hydrogen isotope variation in oceanic pelagic seabirds - Peggy H. Ostrom; Anne E. Wiley; Sam Rossman; Craig A. Stricker; Helen F. James (Oecologia, 2014)

Bridging Disciplines, Knowledge Systems and Cultures in Pest Management - Will Allen; Shaun Ogilvie; Helen Blackie; Des Smith; Shona Sam; James Doherty; Don McKenzie; James Ataria; Lee Shapiro; Jamie MacKay; Elaine Murphy; Chris Jacobson; et al. (Environmental Management, 2014)

Effect of land-use conversion from forest to cocoa agroforest on soil characteristics and quality of a Ferric Lixisol in lowland humid Ghana - Evans K. Dawoe; James S. Quashie-Sam; Samuel K. Oppong (Agroforestry Systems, 2014)

Towards improved socio-economic assessments of ocean acidification’s impacts - Nathalie Hilmi; Denis Allemand; Sam Dupont; Alain Safa; Gunnar Haraldsson; Paulo A. L. D. Nunes; Chris Moore; Caroline Hattam; Stéphanie Reynaud; Jason M. Hall-Spencer; Maoz Fine; Carol Turley; et al. (Marine Biology, 2013)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Effects of Commonly Used Excipients on the Expression of CYP3A4 in Colon and Liver Cells - Leslie Tompkins; Caitlin Lynch; Sam Haidar; James Polli; Hongbing Wang (Pharmaceutical Research, 2010)

Diversity and host specificity of the Verminephrobacter –earthworm symbiosis - Marie B. Lund; Seana K. Davidson; Martin Holmstrup; Sam James; Kasper U. Kjeldsen; David A. Stahl; Andreas Schramm (Environmental Microbiology, 2010)
Summary Symbiotic bacteria of the genus Verminephrobacter ( Betaproteobacteria ) were detected in the nephridia of 19 out of 23 investigated earthworm species ( Oligochaeta : Lumbricidae ) by 16S rRNA gene sequence analysis and fluorescence in situ hybridization (FISH). While all four Lumbricus species and three out of five Aporrectodea species were densely colonized by a mono‐species culture of Verminephrobacter , other earthworm species contained mixed bacterial populations with varying proportions of Verminephrobacter ; four species did not contain Verminephrobacter at all. The Verminephrobacter symbionts could be grouped into earthworm species‐specific sequence clusters based on their 16S rRNA and RNA polymerase subunit B ( rpoB ) genes. Closely related host species harboured more closely related symbionts than did distantly related hosts. Co‐diversification of the symbiotic partners could not be demonstrated unambiguously due to the poor resolution of the host phylogeny [based on histone H3 and cytochrome c oxidase subunit I (COI) gene sequence analyses]. However, there was a pattern of symbiont diversification within four groups of closely related hosts. The mean rate of symbiont 16S rRNA gene evolution was determined using a relaxed clock model, and the rate was calibrated with paleogeographical estimates of the time of origin of Lumbricid earthworms. The calibrated rates of symbiont 16S rRNA gene evolution are 0.012–0.026 substitutions per site per 50 million years and thus similar to rates reported from other symbiotic bacteria.

Litterfall and litter nutrient dynamics under cocoa ecosystems in lowland humid Ghana - Evans K. Dawoe; Marney E. Isaac; James Quashie-Sam (Plant and Soil, 2010)

Distribution of anuran amphibians in massively altered landscapes in south‐eastern Australia: effects of climate change in an aridifying region - Ralph Mac Nally; Gregory Horrocks; Hania Lada; P. Sam Lake; James R. Thomson; Andrea C. Taylor (Global Ecology and Biogeography, 2009)
Aim We explored whether the anuran amphibian faunas differed among landscapes that are relatively intact (largely covered in forests and woodlands) and others that are completely converted to agriculture. We also used historical data sets to assess the current condition of the anuran fauna in a region predicted to experience, and experiencing, severe drying and warming. Location Five pairs of landscapes (each of c . 20 km 2 ) – one in each pair being almost completely wooded and the other cleared for agriculture – across a 30,000 km 2 region of northern Victoria, Australia. Methods Sites were repeatedly surveyed in the austral winter–spring breeding seasons of 2006 and 2007, with records collected of numbers of calling males and the presence of egg masses and tadpoles. We characterized the sites using static (e.g. dimensions, surrounding physiognomic characteristics such as tree cover) and labile (e.g. pH, dissolved oxygen) variables. Data were analysed using hierarchical Bayesian models. Results For calling males, landscape type did not affect densities or species richness measures. The availability of a grassy verge around water bodies was an important predictor for most species, but other labile and static variables seemed not to be important. Fewer than half of the species historically known from the region were recorded. There were no important predictors of occurrence of egg masses or tadpoles. Reproduction effectively may have failed over the period, with fewer than one in four sites showing evidence of egg masses or tadpoles. Main conclusions The proportion of sites at which some well‐studied species (e.g. Crinia signifera , Limnodynastes dumerilii ) were recorded has dropped substantially since the 1970s, as have average densities of calling males of Crinia spp. The remnant anuran fauna appears to be dominated by resilient and hardy species with low current diversity. The on‐going (12+ years) drought in these landscapes suggests a bleak long‐term prognosis for the few remaining species of anuran amphibians.

The challenge of providing plant pest diagnostic services for Africa - Julian J. Smith; Jeff Waage; James W. Woodhall; Sam J. Bishop; Nicola J. Spence (European Journal of Plant Pathology, 2008)

Vegetation along hydrologic, edaphic, and geochemical gradients in a high-elevation poor fen in Canaan Valley, West Virginia - James S. Rentch; James T. Anderson; Sam Lamont; John Sencindiver; Robert Eli (Wetlands Ecology and Management, 2008)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

Monitoring food web changes in tide-restored salt marshes: A carbon stable isotope approach - Andrew S. Wozniak; Charles T. Roman; Sam C. Wainright; Richard A. McKinney; Mary-Jane James-Pirri (Estuaries and Coasts, 2006)